Hak Kewajiban dan Tanggung Jawab Guru Dalam Pendidikan Indonesia - Hidayat Hidayat; Hilalludin Hilalludin (Lembaga Pengembangan Kinerja Dosen, 2024)
This study explores the rights and responsibilities of teachers as defined by various Indonesian laws and regulations, particularly Law No. 14 of 2005 concerning Teachers and Lecturers. The research underscores the significance of understanding these aspects to ensure the quality of education. The objective is to identify and analyze teachers' rights, responsibilities, and duties in fulfilling their professional roles. The methodology employed is a literature review or library research, involving data collection from diverse library sources including books, encyclopedias, documents, and scholarly journals. The findings reveal that teachers' rights encompass adequate income, career development, welfare benefits, legal protections, and freedoms of organization and expression. Meanwhile, teachers' responsibilities include planning, implementing, assessing, and evaluating quality learning, as well as continuous enhancement of academic qualifications. The study concludes that a comprehensive grasp of teachers' rights and responsibilities enhances professionalism and educational standards in Indonesia. The implications highlight the need for robust regulatory frameworks and policies to support teachers in performing optimally and competing globally.